An intelligent navigation system for oil palm plantations - Juman, Mohammed Ayoub (2019)
In order to introduce automation to oil palm plantations as a solution to a reduction in workforce, a smart navigation system capable of operating autonomously was required. This thesis focuses on the creation of an intelligent navigation system for oil palm plantations. For the successful creation of the system, an object detection system to detect tree trunks, a path planner to calculate the optimum path to the tree and a trajectory controller to accurately move along the path was necessary. A robot rover was designed and built to test the created system, and novelties were presented in the object detection as well as the trajectory control systems to tackle the difficulties faced due to the plantation environment.